2008
DOI: 10.1002/smi.1241
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with a ‘hidden stressor’: emotional disclosure as a coping strategy to overcome the negative effects of motive incongruence on health

Abstract: Summary Taking the affi liation motive as an example, present research examines whether the negative effects of implicit-explicit motive incongruence on health is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Our present findings are in line with the conclusion by McClelland et al (1989) as well as with many findings that incongruence between implicit and explicit motives has negative effects, regardless of the direction of the discrepancy (Baumann et al, 2005;Kehr, 2004;Schüler, Job, Fröhlich, & Brandstätter, 2009;see Brunstein, 2010, for an overview).…”
Section: Discussionsupporting
confidence: 93%
“…Our present findings are in line with the conclusion by McClelland et al (1989) as well as with many findings that incongruence between implicit and explicit motives has negative effects, regardless of the direction of the discrepancy (Baumann et al, 2005;Kehr, 2004;Schüler, Job, Fröhlich, & Brandstätter, 2009;see Brunstein, 2010, for an overview).…”
Section: Discussionsupporting
confidence: 93%
“…Incongruence between implicit and explicit motives, in contrast, has been characterized as ''striving for goals without gaining pleasure from doing so'' or ''a lack of striving for goals which would give rise to positive affect'' (Langens and McClelland 1997;cf. Kazén and Kuhl 2011) and found to impinge on well-being and health as a hidden stressor across the social motives of affiliation (Schüler et al 2009), achievement , and power (Hofer et al 2010). found that people high in action orientation are better able to attune the explicit achievement motive to the implicit achievement motive.…”
Section: Action Orientation and Motive Congruencementioning
confidence: 93%
“…Higher motive incongruence scores thus indicate higher incongruence between implicit and explicit achievement motives. Previous research has demonstrated high validity of motive-incongruence scores (e.g., Baumann et al 2005;Clavadetscher 2003;Kehr 2004;Schüler et al 2009; for similar self-discrepancy measures, see for example Boldero and Francis 2000;Brunstein et al 1998;Higgins 1998). A motive-incongruence score makes theoretical sense when the phenomenon of motive incongruence itself is subject to examination, that is, when the assumption is made that both types of motive incongruence (a high explicit motive combined with a low implicit motive as well as a high implicit motive combined with a low explicit motive) cause intrapersonal motive conflicts that result in impaired physiological and subjective well-being (for a similar line of reasoning, see Baumann et al 2005;Kehr 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Common to many explanations of the negative effects of motive incongruence is some form of intrapersonal conflict or stress (Brunstein et al 1998;McClelland and Jemmott 1980;Kehr 2004;McAdams and Bryant 1987;Schüler et al 2009). Either a high implicit motive is not satisfied by behavior which is elicited by a high explicit motive, (e.g., by the personal goals of a person) or a high explicit motive is not supported by the energy which is exerted in connection with a high implicit motive, so that goal attainment requires extra volitional energy and is exhausting.…”
Section: Motive Incongruence and Its Negative Effectsmentioning
confidence: 99%